Społeczne zaangażowanie biznesu na przykładzie firmy PricewaterhouseCoopers - Teneta-Skwiercz, Dorota (Corporate Community Involvement In PricewaterhouseCoopers, 2008)
The article focuses on the idea of Corporate Community Involvement (CCI). In the first part of it the author defines not only the heart of the matter but also its premises. Besides there are also advantages and benefits mentioned which may be gained by workers and society generally understood -and all of it in the environment of the corporate responsible company. The second part of the article consists of describing vast variety of enterprises within CCI which have been executed by PricewaterhouseCoopers.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 396-403